BENTUK REDUPLIKASI PADA CERPEN DAN DONGENG DALAM MAJALAH BOBO EDISI 12 TAHUN 2017 - Athya Zelmifa Nasty; Ida Basaria; Fitri Qodariyah Siregar; Metha Alyona Alphonse Silalahi (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2024)
This research aims to explain the form of reduplication in the rubric of short stories and fairy tales in Bobo children's magazine Edition 12 Year 2017. The research used is qualitative research, which collects all repetitive words in Bobo magazine. in Bobo magazine Edition 12 Year 2017. The method used in data analysis data analysis is agih method with data collection techniques in the form of listening and note-taking techniques. note technique. After the research, five forms of reduplication were found: 1) dwilingga; 2) dwilingga salin suara; 3) dwipurwa; 4) dwiwasana; and 5) reduplication with affixes. Keywords: reduplication, short stories and tales, magazine